Regional Governance bei Gemeinschaftsgütern des Ressourcenschutzes: das Beispiel Biosphärenreservate - Fürst, Dietrich; Lahner, Marion; Pollermann, Kim (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The article discusses the potentials of using patterns of regional governance for natural resource management (e.g. water, nature protection, landscape formation). The empirical basis refers to biosphere reserves. After clarifying shortly the main concepts used (regional governance, collective goods, place-making, biosphere reserve) and after summarizing the sparse literature on the subject the article discusses the lead question on the basis of the approach of “actor-centred institutionalism” (Scharpf). Linking the concept back to empirical findings we come to the conclusion that Regional governance is principally possible and effective if supported by place-identity of regional actors and promotors to channel the resulting powers into collective actions.